The Effectiveness of Using BPN's Land Check Application to Avoid Misuse of Sea Fence Certificates in Indonesia - Hakim, Lukmanul (Sultan Agung Notary Law Review, 2025)
One of the institutions that has a close relationship with land is the National Land Agency (BPN) which is regulated in Government Regulation No. 10 of 2006 concerning the National Land Agency. It is explained in Article 1 paragraph 1 of PP No. 10 of 2006 that the National Land Agency is a Non-Departmental Government Institution that is under and responsible to the president. Furthermore, in Article 2 of PP No. 10 of 2006 it is stated that the National Land Agency has the task of carrying out government duties in the land sector nationally, regionally and sectorally. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency continues to make various breakthroughs and innovations by utilizing information and communication technology. One of the innovations that has been implemented is the Electronic Certificate Checking Service. The Electronic Certificate Checking Service is one form of innovation in improving services in the land sector so that BPN services become effective, efficient, transparent, and inexpensive. In Indonesia, constitutionally, land issues as the surface of the earth are regulated in Article 33 paragraph (3) of the 1945 Constitution, which reads: "The land and water and the natural resources contained therein are controlled by the State and used for the greatest prosperity of the people". The research method used in this study is doctrinal legal research, which uses a juridical-normative approach in discussing legal norms. The doctrinal legal research method is carried out by involving the study of existing legal materials such as laws and regulations under them, jurisprudence, and existing legal concepts. This research focuses on the analysis, interpretation, and synthesis of law to answer legal questions or develop a legal theory.